The Buddha's wizards : magic, protection, and healing in Burmese Buddhism - Patton, Thomas Nathan (New York : Columbia University Press, 2018)
Belief in wizard-saints who protect their devotees and intervene in the world is widespread among Burmese Buddhists. The Buddha's Wizards is a historically informed, ethnographic study that explores the supernatural landscape of Buddhism in Myanmar to explain the persistence of wizardry as a form of lived religion in the modern era.
Vanguards of the Sāsana -- The Buddha's chief wizard -- Women of the wizard king -- Pagodas of power -- Wizards in the shadows.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072
Keywords: Buddhism -- Burma; Burma -- Religious life and customs; Wizards -- Burma; Occultism -- Burma; Buddhism; Occultism; Burma; RELIGION / Comparative Religion; HISTORY / Asia / Southeast Asia; Electronic books